Recombinant pro-CTSD (cathepsin D) enhances SNCA/α-Synuclein degradation in α-Synucleinopathy models. - Huarcaya, Alice Prieto; Drobny, Susy; Marques, Andre R. A.; Di Spiezio, Alessandro; Dobert, Jan; Balta, Denise; Werner, Christian; Rizo Garza, Tania; Gallwitz, Lisa; Bub, Simon; Stojkovska, Iva; Belur, Nandkishore R.; et al. (Autophagy, 2022)
Parkinson disease (PD) is a neurodegenerative disorder characterized by the abnormal intracellular accumulation of SNCA/α-synuclein. While the exact mechanisms underlying SNCA pathology are not fully understood, increasing evidence suggests the involvement of autophagy as well as lysosomal deficiencies. Because CTSD (cathepsin D) has been proposed to be the major lysosomal protease involved in SNCA degradation, its deficiency has been linked to the presence of insoluble SNCA conformers in the brain of mice and humans as well as to the transcellular transmission of SNCA aggregates. We here postulate that SNCA degradation can be enhanced by the application of the recombinant human proform of CTSD (rHsCTSD). Our results reveal that rHsCTSD is efficiently endocytosed by neuronal cells, correctly targeted to lysosomes and matured to an enzymatically active protease. In dopaminergic neurons derived from induced pluripotent stem cells (iPSC) of PD patients harboring the A53T mutation within the SNCA gene, we confirm the reduction of insoluble SNCA after treatment with rHsCTSD. Moreover, we demonstrate a decrease of pathological SNCA conformers in the brain and within primary neurons of a ctsd-deficient mouse model after dosing with rHsCTSD. Boosting lysosomal CTSD activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function. Our findings indicate that CTSD is critical for SNCA clearance and function. Thus, enzyme replacement strategies utilizing CTSD may also be of therapeutic interest for the treatment of PD and other synucleinopathies aiming to decrease the SNCA burden.Abbreviations: aa: amino acid; SNCA/α-synuclein: synuclein alpha; APP: amyloid beta precursor protein; BBB: blood brain barrier; BF: basal forebrain; CBB: Coomassie Brilliant Blue; CLN: neuronal ceroid lipofuscinosis; CNL10: neuronal ceroid lipofuscinosis type 10; Corr.: corrected; CTSD: cathepsin D; CTSB: cathepsin B; DA: dopaminergic; DA-iPSn: induced pluripotent stem cell-derived dopaminergic neurons; dox: doxycycline; ERT: enzyme replacement therapy; Fx: fornix, GBA/β-glucocerebrosidase: glucosylceramidase beta; h: hour; HC: hippocampus; HT: hypothalamus; i.c.: intracranially; IF: immunofluorescence; iPSC: induced pluripotent stem cell; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LSDs: lysosomal storage disorders; MAPT: microtubule associated protein tau; M6P: mannose-6-phosphate; M6PR: mannose-6-phosphate receptor; MB: midbrain; mCTSD: mature form of CTSD; neurofil.: neurofilament; PD: Parkinson disease; proCTSD: proform of CTSD; PRNP: prion protein; RFU: relative fluorescence units; rHsCTSD: recombinant human proCTSD; SAPC: Saposin C; SIM: structured illumination microscopy; T-insol: Triton-insoluble; T-sol: Triton-soluble; TEM: transmission electron microscopy, TH: tyrosine hydroxylase; Thal: thalamus.
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomal storage disorders; parkinson disease; synucleinopathies

SARS-CoV-2 Spike Protein Induces Time-Dependent CTSL Upregulation in HeLa Cells and Alveolarspheres - Bolsinger, Magdalena; Drobny, Alice; Wilfling, Sibylle; Reischl, Stephanie; Krach, Florian; Moritz, Raul; Balta, Denise; Hehr, Ute; Sock, Elisabeth; Bleibaum, Florian; Hanses, Frank; Winner, Beate; et al. (Journal of Cellular Biochemistry, 2024)
Autophagy and lysosomal pathways are involved in the cell entry of SARS-CoV-2 virus. To infect the host cell, the spike protein of SARS-CoV-2 binds to the cell surface receptor angiotensin-converting enzyme 2 (ACE2). To allow the fusion of the viral envelope with the host cell membrane, the spike protein has to be cleaved. One possible mechanism is the endocytosis of the SARS-CoV-2–ACE2 complex and subsequent cleavage of the spike protein, mainly by the lysosomal protease cathepsin L. However, detailed molecular and dynamic insights into the role of cathepsin L in viral cell entry remain elusive. To address this, HeLa cells and iPSC-derived alveolarspheres were treated with recombinant SARS-CoV-2 spike protein, and the changes in mRNA and protein levels of cathepsins L, B, and D were monitored. Additionally, we studied the effect of cathepsin L deficiency on spike protein internalization and investigated the influence of the spike protein on cathepsin L promoters in vitro. Furthermore, we analyzed variants in the genes coding for cathepsin L, B, D, and ACE2 possibly associated with disease progression using data from Regeneron's COVID Results Browser and our own cohort of 173 patients with COVID-19, exhibiting a variant of ACE2 showing significant association with COVID-19 disease progression. Our in vitro studies revealed a significant increase in cathepsin L mRNA and protein levels following exposure to the SARS-CoV-2 spike protein in HeLa cells, accompanied by elevated mRNA levels of cathepsin B and D in alveolarspheres. Moreover, an increase in cathepsin L promoter activity was detected in vitro upon spike protein treatment. Notably, the knockout of cathepsin L resulted in reduced internalization of the spike protein. The study highlights the importance of cathepsin L and lysosomal proteases in the SARS-CoV-2 spike protein internalization and suggests the potential of lysosomal proteases as possible therapeutic targets against COVID-19 and other viral infections.
CRIS-Team Scopus Importer:2024-07-19
Keywords: cathepsin L; cathepsins; lysosomes; SARS-CoV-2; spike protein

The role of lysosomes in alpha-synucleinopathies: A focus on glial cells - Balta, Denise; Zunke, Friederike (Neural Regeneration Research, 2022)
CRIS-Team Scopus Importer:2022-01-07

The role of triggering receptor expressed on myeloid cells 2 in Parkinson's disease and other neurodegenerative disorders - Schwarz, Hannah; Bässler, Sarah; Balta, Denise; Socher, Eileen; Zunke, Friederike; Arnold, Philipp (Behavioural Brain Research, 2022)
Parkinson's disease (PD) is a progressive neurological disorder marked by cardinal clinical symptoms such as rigor, tremor, and akinesia. Albeit a loss of dopaminergic neurons from the substantia nigra pars compacta is causative for the movement impairments found in patients, molecular reasoning for this loss is still incomplete. In recent years, triggering factor expressed on myeloid cells (TREM2) gained attention in the field of neurodegeneration as it could be associated with different neurodegenerative disorders. Primarily identified as a risk factor in Alzheimer's disease, variants in TREM2 were linked to PD and multiple sclerosis, too. Expressed on phagocytic cells, such as macrophages and microglia, TREM2 puts the focus on inflammation associated conditions in PD and provides a molecular target that could at least partly explain the role of immune cells in PD. Here, we summarize expression patterns and molecular functions of TREM2, recapitulate on its role in inflammation, phagocytosis and cell survival, before turning to neurodegenerative disorders with an emphasis on PD.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Cell signaling; DAP12; Inflammation; Neurodegeneration; Parkinson's disease; TREM2